M. tuberculosis microvariation is common and is associated with transmission: analysis of three years prospective universal sequencing in England - Wyllie, DH; Do, T; Myers, R; Nikolayevsky, V; Crook, D; Peto, T; Alexander, E; Robinson, E; Walker, AS; Campbell, C; Smith, GE (Elsevier, 2022)
Background: The prevalence, association with disease status, and public health impact of infection with mixtures of M. tuberculosis strains is unclear, in part due to limitations of existing methods for detecting mixed infections.